A análise da aposentadoria especial, com ênfase na prova do exercício de atividades sob condições especiais - Amaro, Kátia Helena Fernandes Simões (2012)
This thesis aims to critical study of the historical evolution of the rule that ensures the provision of special retirement in Brazil, having as its main focus the examination of evidence available to the insured to demonstrate the performance of activities under special conditions, as well understood as the work where there is exposure to aggressive agents to their health or physical integrity of the insured, both in administrative proceedings and in pension lawsuit